The history of rock & roll - Shirley, David, 1955- (New York : F. Watts, 1997)
Traces the history of rock and roll music from the 1950s to the present day and discusses its changing styles and leading personalities.
Cover title: History of rock and roll.
Includes bibliographical references (p. 156), discographies (p. 157-166) and index.
Booklist.
L.A. Recommended Foreign Language.
Voice of Youth Advocates (V.O.Y.A.).
Young Adult
Keywords: Rock music -- History and criticism -- Juvenile literature; Rock music -- History and criticism; Rock music -- History and criticism